Kualitas Silase Ransum Komplit Berbahan Baku Pakan Lokal - Allaily Allaily; Nahrowi Ramli; R. Ridwan (Jurnal Agripet, 2011)
The quality of complete ration silage use traditional local feed materialsABSTRACT. The research was conducted to assess the complete ration silage products use traditional local feed materials of high water levels are currently still problematic in storage. The technology used is in a state of anaerobic fermentation technology. This study uses a random group, with 4 levels of water treatment (30, 40, 50, and 60%) and 4 groups of storage time (1, 2, 3, and 4 weeks) at room temperature, each unit of treatment was repeated 3 times. Silage made in a glass bottle filled with 200-300 g of feed a complete and total BAL plus Lactobacillus plantarum 105 cfu per gram of silage. Physically and chemically, products made from raw silage rations complete local feed has characteristics that are not much different from the silage forage. Water content and storage time is very significant (P 0.01) lower pH and increased total acids.